Community-Based Tourism Development at the East Coast of Phuket Island (Tambon Maikhao, Tambon Paklok, Tambon Kohkeaw, and Tambon Rasada) - Bandit Santikul (Prince of Songkla University, 2016)
Thesis (M.B.A., Hospitality and Tourism Management (International Program)--Prince of Songkla University, 2010